Developing spatial map of landscape trees at UMK Jeli campus using GIS. Issue 1 (August 2021) - Daliman, S; Tan, R; Amaludin, N A
Abstract: Landscape trees are wood's trees that had been planted artificially within the urban areas. For affection management and preservation purposes, a spatial map of these tree have been developed for landscape trees at UMK Jeli Campus using GIS. The scope of this study is focusing on conducting tree inventory for landscape trees planted surrounding the main infrastructure and building at UMK Jeli Campus. Due to the limitation of published existing data and recording about landscape inventories of UMK Jeli Campus and the existing data are incomplete, the objective of the study is to create a database and spatial tree map of those landscape trees of the campus using GPS and GIS software through tree inventory. The database and spatial tree map are significantly importance as it can be used for future management and planning of the landscape and landscape trees of the campus. The process of this study began by performing tree inventory to collect the spatial ground information of the landscape trees inside the campus. Plants identification Apps of Pl@ntNet Identify will be used to identify the scientific species name of the landscape trees, then combining both information to create a database. The database shall be displayed into ArcGIS software by overlapping with the digital image of UMK Jeli Campus to develop a spatial tree map. As a result, the total of 22 areas that marked for tree inventory had been established with the collected total number of 1466 sites of landscape trees and 83 different types of species been sampled and collected their data during the tree inventory.